Auxiliary techniques for the diagnosis of incipient interproximal caries, in deciduous molars of children from 4 to 10 years old - Pardo Salas, Jessica (2018)
Objective: The incipient carious lesion known for their clinical characteristics like white opaque after drying shows a rough surface, this is the first evidence of caries which is actively and visible on the surface of the dental tissue observed in a pit and fissure, proximal surfaces near the contact point along the gingival margin, in relation to the proximal surfaces by having a difficult accessibility, just by visual inspection is a big obstacle, so the objective of this study is identify the auxiliary a proximal decay incipient technique with improved an outcome to diagnosis in primary molars. Materials and Methods: A transversal and descriptive study was performed. The sample was composed by 50 children from 4-10 years old. A medical history was applied, which recorded all the dental information about the diagnosis, taking into account the criteria according to ICDAS in 2005. The examination was took place various sessions, a prophylaxis was previously performed, for this study we used an oral mirror, magnifying glass, a type of viscera which increased (3.5X), LED lamp and per apical bitewing x-rays. Results: A significant difference in efficacy for detection of interproximal caries lesions among emerging techniques evaluated were found.  Conclusion: A 3.5X magnification technique made it possible to detect more caries lesions in primary molars with a total of 69. Followed by visual and radiographic being Trans illuminations which had the lowest levels of effectiveness.